Motor learning in dystonia: distorted feedback results in distorted motor learning and information-seeking compensatory behaviour. Issue 3 (September 2018) - Nagy, Edit
Abstract : Motor learning is possible in dystonia, but distorted feedback results in distorted motor performance and information-seeking compensatory behavior, as observed in this case. With globus pallidus internal segment deep brain stimulation, the postural background of hand writing improved, but the learned left compensatory grip did not change.